2015
DOI: 10.15537/smj.2015.6.11153
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against human platelet alloantigens and human leucocyte antigen class 1 in Saudi Arabian multiparous women and multi-transfused patients

Abstract: Objectives:To determine the frequency of alloimmunization against human platelet antigens (HPAs) and human leucocyte antigen class 1 (HLA1) in multiparous women and multi-transfused patients.Methods:This prospective study was conducted between January and August 2013, on 50 multiparous women with no history of previous blood transfusion recruited from the Obstetrics and Gynecology Clinic, and 50 patients, who received multiple platelet transfusions, recruited from the Hematology/Oncology Ward, King Khalid Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Anti‐HLA class I antibodies causing PTR is a common and serious complication of alloimmunised patients receiving long‐term platelet transfusions (Cid et al ., ). In this study, the rate of alloimmunisation was 114 of 204 (55.88%), which was close to that of many earlier publications (Table ) (Economidou et al ., ; Friedman et al ., ; Kurz et al ., ; Ferreira et al ., ; Al‐Ouda et al, ), including 112 of 114 (98.25%) caused by anti‐HLA class I antibodies. As most of platelet transfusion refractory patients had haematological diseases, we showed that the antibody‐positive rate was significantly different between the haematological disease group and the other disease group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti‐HLA class I antibodies causing PTR is a common and serious complication of alloimmunised patients receiving long‐term platelet transfusions (Cid et al ., ). In this study, the rate of alloimmunisation was 114 of 204 (55.88%), which was close to that of many earlier publications (Table ) (Economidou et al ., ; Friedman et al ., ; Kurz et al ., ; Ferreira et al ., ; Al‐Ouda et al, ), including 112 of 114 (98.25%) caused by anti‐HLA class I antibodies. As most of platelet transfusion refractory patients had haematological diseases, we showed that the antibody‐positive rate was significantly different between the haematological disease group and the other disease group.…”
Section: Discussionmentioning
confidence: 99%
“…Austria (Kurz et al, 1996) 54.00 -Saudi Arabia (Al-Ouda et al, 2015) 42.00 2-124 (43.75%) and anti-HLA-C07 (25.00%), which is consistent with our previous study that described the most common HLA-A and HLA-B alleles in our donor registry (Xia et al, 2010). In light of the findings presented, this study demonstrates that if the patient has HLA Class I antibodies to high-frequency antigens, it is increasingly difficult for them to receive suitable platelet units through cross-match assays.…”
Section: Discussionmentioning
confidence: 99%